Comparison of 25-Hydroxyvitamin D Levels in Acute Coronary Syndrome - Mirna Rahmafindari; Leonita Anniwati; Muh. Aminuddin; Ferdy R. Marpaung (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Vitamin D deficiency is associated with cardiovascular disease, one of, which is an Acute Coronary Syndrome (ACS). Some studies provide varying results, the 25 (OH)D levels, which can cause acute coronary syndrome is still controversial. This was an observational analytical study with a cross-sectional design. Samples were collected during April-September 2019 from the Dr. Soetomo Hospital, Surabaya. Patients with the acute coronary syndrome (70 persons) consisted of ST-Elevation Myocardial Infarction (STEMI), non-ST-Elevation Myocardial Infarction (NSTEMI), Unstable Angina (UA) were measured for 25 (OH)D and the differences in levels of 25 (OH)D between groups. Examination of 25 (OH)D used a competitive antibody method chemiluminescence immunoassay. There were different levels of 25 (OH)D patients with ACS versus healthy persons, p=0.0001. There was no difference in levels of 25 (OH)D in UA patients versus healthy persons, p=0.925. Acute coronary syndrome patients had higher 25 (OH)D levels than healthy persons, so it seemed that vitamin D did not play an essential role in the occurrence of ACS based on this study. This study showed that there were significant differences between 25 (OH)D levels in STEMI and healthy persons, NSTEMI and healthy persons, STEMI and NSTEMI, STEMI and UA, NSTEMI and UA. In the UA group and healthy persons, no statistically significant differences were found.